1996
DOI: 10.1074/jbc.271.24.14567
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Novel Thyroid Hormone-responsive Gene, , in Human Skin Fibroblasts

Abstract: Utilizing a method called "differential display of mRNAs by means of polymerase chain reaction", the cDNA fragment of a thyroid hormone-responsive gene ZAKI-4 was cloned from cultured human skin fibroblasts. Northern blot analysis revealed that there were two ZAKI-4 mRNA species (3.4 and 1.4 kilobases (kb)), and they were up-regulated by a physiological concentration of triiodothyronine (T3). This T3 effect was abolished by the treatment with cycloheximide, indicating the possibility that gene ZAKI-4 is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
68
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 21 publications
6
68
0
Order By: Relevance
“…Therefore, we suggest that ''modulatory'' calcineurin-interacting protein may be a more appropriate term. Two other members of the MCIP gene family, MCIP2 and MCIP3, are not located on chromosome 21 (13,14). MCIP1 and MCIP2 are expressed at the highest levels in striated muscles and brain, whereas MCIP3 is expressed at a low level in a broad range of tissues.…”
mentioning
confidence: 99%
“…Therefore, we suggest that ''modulatory'' calcineurin-interacting protein may be a more appropriate term. Two other members of the MCIP gene family, MCIP2 and MCIP3, are not located on chromosome 21 (13,14). MCIP1 and MCIP2 are expressed at the highest levels in striated muscles and brain, whereas MCIP3 is expressed at a low level in a broad range of tissues.…”
mentioning
confidence: 99%
“…Individuals trisomic for this region, which is estimated to encode 50 -100 different proteins, display features of the Down syndrome phenotype. ZAKI-4 was identified from a human fibroblast cell line in a screen for genes that are transcriptionally activated in response to thyroid hormone (26). We were stimulated by these observations to undertake a detailed analysis of the proteins encoded by these genes with respect to calcineurin signaling in mammalian cells.…”
mentioning
confidence: 99%
“…Calcineurin is known to mediate important functions of the brain, such as neuronal apoptosis, amyloid b-peptide formation, synaptic plasticity and memory [reviewed in 25]. Since we have previously shown that ZAKI-4 mRNA is expressed in the human brain, as well as in heart and skeletal muscles [18], we hypothesize that ZAKI-4 proteins play a crucial role in those tissues by inhibiting calcineurin activity.…”
Section: Introductionmentioning
confidence: 98%
“…ZAKI-4 proteins (also designated as DSCR1L1 by the Human Nomenclature Committee) are products of the ZAKI-4 gene which we previously identified as a thyroid hormoneresponsive gene from cultured human skin fibroblasts [18]. In human fibroblasts, the transcription of the ZAKI-4 gene is markedly enhanced by physiological concentrations of 3,3'5-triiodothyronine (T 3 ), an active form of thyroid hormone; however, the enhancement is not direct and requires de novo protein synthesis [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation